BAIBA Does Not Regulate UCP-3 Expression in Human Skeletal Muscle as a Response to Aerobic Exercise. (3rd April 2017) - Morales, Flor E.; Forsse, Jeffrey S.; Andre, Thomas L.; McKinley-Barnard, Sarah K.; Hwang, Paul S.; Anthony, Ian G.; Tinsley, Grant M.; Spillane, Mike; Grandjean, Peter W.; Ramirez, Alejandro; Willoughby, Darryn S.
ABSTRACT: Objective : β-Aminoisobutyric acid (BAIBA) has shown to modulate uncoupling protein (UCP)-1 expression, which is mainly expressed in white adipose tissue; however, no studies to date have analyzed its potential effect on the main uncoupling protein of skeletal muscle, UCP-3. The main goal of this study was to assess the potential effect of acute aerobic exercise on serum BAIBA and skeletal muscle UCP-3. The secondary goal was to assess the potential involvement of the transcription factors proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) and peroxisome proliferator–activated receptor alpha (PPARα), as well as free fatty acids (FFAs) in UCP-3 expression. A tertiary goal of the study was to evaluate the potential effect of consuming a preexercise meal on the outcome of the first 2 objectives. Methods : In a randomized crossover design, untrained participants performed 2 acute cycling sessions (350 kcal at 70% of their VO2peak ) after 2 experimental conditions: (1) consumption of a multi-macronutrient shake and (2) a fasting period of 8 hours. Blood samples were taken at baseline, preexercise, postexercise, 1 hour, and 4 hours postexercise, and muscle biopsies were taken at the last 4 time points. UCP-3 protein concentration and expression, as well as the mRNA expression of PGC-1α and PPARα, were measured in muscle, and BAIBA, glucose, and FFA were measured in serum. Results : Aerobic exercise failed to induce a significant effect on serum BAIBA, PGC-1α, and PPARα regardless on the feeding condition. Despite the lack of effect of exercise on the previous variables, UCP-3 expression and protein concentration significantly increased in the shake condition. Conclusion : The expression of human skeletal muscle UCP-3 as a result of exercise might be controlled by factors other than BAIBA.